Analysis Competitiveness of Corn Farming In South Lampung Regency - Sri Puji Lestari; Dyah aring Hepiana Lestari; Zainal Abidin (Politeknik Negeri Lampung, 2020)
This study aimed to analyze the competitiveness of corn farming in South Lampung Regency. This research was conducted in Penengahan and Ketapang Districts, South Lampung Regency. The respondents in this study were 71 farmers; 48 farmers from Ketapang District and 23 farmers from Penengahan District. The respondents in this study were chosen randomly. Analysis of the competitiveness of corn farming in South Lampung Regency employed the PAM (Policy Analysis Matrix) method. The results showed that corn farming in South Lampung Regency has already had competitiveness (PCR = 0.54 and DRCR = 0.80). The government policies such as fertilizer subsidies, reduction in the amount of corn imports, and corn import tax of 5 percent had protected domestic corn’s farmers.